2018
DOI: 10.1021/acs.orglett.8b03015
|View full text |Cite
|
Sign up to set email alerts
|

Cascade C–H Annulation Reaction of Benzaldehydes, Anilines, and Alkynes toward Dibenzo[a,f]quinolizinium Salts: Discovery of Photostable Mitochondrial Trackers at the Nanomolar Level

Abstract: Fluorescent mitochondrial trackers with the dibenzo[a,f ]quinolizinium core are unprecedentedly synthesized by a one-pot protocol starting from commercially available benzaldehydes, anilines, and alkynes through a rhodium(III)-catalyzed cascade C−H Nand C-annulation reaction. Among them, 5g is the most prominent and exhibits high specificity, high efficiency at nanomolar level, superior photostability, and low cytotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…13 C NMR (125 MHz, CDCl3) δ 191.98, 147.24, 139.75, 135.22, 130.30, 129.04, 128.50, 127.72, 127.39. The spectral data matched those reported in the literature(Kadam et al, 2018).4-(Trifluoromethyl)benzoic acid and phenylboronic acid (3d, Figure 3, Entry 4)According to the general procedure, the reaction of 4-(trifluoromethyl)benzoic acid (0.20 mmol), phenylboronic acid (2.0 equiv), Pd(OAc)2 (5 mol%), 1,4-bis(diphenylphosphino)butane (10 mol%), triethylamine (1.5 equiv), H3BO3 (1.5 equiv) and trimethylacetic anhydride (1.5 equiv) in 1,4-dioxane (0.20 M) for 15 h at 160 °C, afforded after work-up and chromatography the title compound in 91% yield (40.5 mg). White solid.…”
supporting
confidence: 83%
“…13 C NMR (125 MHz, CDCl3) δ 191.98, 147.24, 139.75, 135.22, 130.30, 129.04, 128.50, 127.72, 127.39. The spectral data matched those reported in the literature(Kadam et al, 2018).4-(Trifluoromethyl)benzoic acid and phenylboronic acid (3d, Figure 3, Entry 4)According to the general procedure, the reaction of 4-(trifluoromethyl)benzoic acid (0.20 mmol), phenylboronic acid (2.0 equiv), Pd(OAc)2 (5 mol%), 1,4-bis(diphenylphosphino)butane (10 mol%), triethylamine (1.5 equiv), H3BO3 (1.5 equiv) and trimethylacetic anhydride (1.5 equiv) in 1,4-dioxane (0.20 M) for 15 h at 160 °C, afforded after work-up and chromatography the title compound in 91% yield (40.5 mg). White solid.…”
supporting
confidence: 83%
“…For example, the reaction of p ‐anisaldehyde and p ‐toluidine with diphenylacetylene at 2.5 mol % loading of 2 b and 90 °C in methanol gave the corresponding isoquinolinium salt in 67 % yield, which is comparable with that for the ruthenium catalyst [( p ‐cymene)RuCl 2 ] 2 , [32] the latter working at higher temperature (110 °C in ethanol). In our case, the increase of the reaction temperature to 120 °C in DCE only slightly increases the yield of the target product (to 70 %) [33] . Complex 2 b also exhibited moderate catalytic activity in the reaction of benzamide with two equivalents of diphenylacetylene to form 8H‐isoquinolino[3,2‐a]isoquinolin‐8‐one in 49 % yield via double CH activation [34] .…”
Section: Resultsmentioning
confidence: 63%
“…In our case, the increase of the reaction temperature to 120°C in DCE only slightly increases the yield of the target product (to 70 %). [33] Complex 2 b also exhibited moderate catalytic activity in the reaction of benzamide with two equivalents of diphenylacetylene to form 8H-isoquinolino [3,2-a]isoquinolin-8-one in 49 % yield via double CH activation. [34] At the same time, the reaction of acetanilide with 1-phenyl-1-propyne catalyzed by 2 b gave the corresponding indole derivative in 25 % yield, which is comparable with that for the classical catalyst [Cp*RhCl 2 ] 2 , [35] but lower than for the functionalized indenyl derivative [(η 5 -5-1-(COOEt)-2-Me-3-benzyl-indenyl)RhI 2 ] 2 .…”
Section: Catalytic Activity Of the Halide Complexes 2 Abmentioning
confidence: 99%
“…This synergy is probably connected to different influences of each of the precursors on cell physiology, such as the effect of free radicals related to the presence of APS. It is reported that aniline derivatives possess, for example, DNA intercalating properties [19]. However, information on this effect exerted by An or AnH are insufficient.…”
Section: Resultsmentioning
confidence: 99%